The role of the mass media in prevention and fight against the corruption - Đinh Trần Dũng (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
For a long time, the mass media has a very important role in the social life in general and in the prevention and fight against corruption in particular. In fact, the majority of corruption cases are "exposed" by the mass media; without the mass media, many cases of corruption will "sink". In modern society, the mass media has been affirmed as a "pioneer" position in the fight against corruption. In the following article, the author will briefly analyze the role of the mass media in anti-corruption.